2015
DOI: 10.1055/s-0035-1560828
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for the Synthesis of Furo-imidazo[3.3.3]propellanes from Thiocarbonohydrazides

Abstract: The Table of contents Title, author's name, address and table of contents S1 Crystallographic Data for Compound 5a S2-S7 Crystallographic Data for Compound 5c S8-S10 Table 10. Hydrogen-bond geometry (Å, º) of 5c

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Hassan et al reported that reaction of equimolar amounts of the thiocarbonohydrazide derivative 155 and the inden‐2‐ylidenepropanedinitrile 151 in tetrahydrofuran, with admission of air and stirring at room temperature, led to the generation of an orange‐colored mixture, which quickly turned reddish‐brown. Continued stirring of the mixture resulted in the precipitation of fine colorless crystals of furo‐imidazo[3.3.3]propellane 158 via the cycloaddition intermediate 157 (Scheme ) .…”
Section: Reactions Of Bis‐thioureasmentioning
confidence: 99%
“…Hassan et al reported that reaction of equimolar amounts of the thiocarbonohydrazide derivative 155 and the inden‐2‐ylidenepropanedinitrile 151 in tetrahydrofuran, with admission of air and stirring at room temperature, led to the generation of an orange‐colored mixture, which quickly turned reddish‐brown. Continued stirring of the mixture resulted in the precipitation of fine colorless crystals of furo‐imidazo[3.3.3]propellane 158 via the cycloaddition intermediate 157 (Scheme ) .…”
Section: Reactions Of Bis‐thioureasmentioning
confidence: 99%
“…Interestingly, furo‐imidazo[3.3.3] propellanes 45a – d were synthesized in 85–92% yields by the reactions of 35a – d with 2‐(1,3‐dioxo‐2,3‐dihydro‐1 H ‐inden‐2‐ylidene)propanedinitrile (CNIND, 44 ) in tetrahydrofuran (THF) as a solvent (Scheme ) .…”
Section: Thiocarbohydrazidesmentioning
confidence: 99%
“…In fact, propellane derivatives are found in many biologically active compounds and natural products . Hassan and co‐workers synthesized novel furo‐imidazo[3,3,3]propellanes 63 viareactions of thiocarbonohydrazides 62 with DCID 61 at room temperature in tetrahydrofuran . The reaction proceeded by the initial attack of NH group of 62 on the electrophilic C=C of 61 to form intermediate A .…”
Section: Introductionmentioning
confidence: 99%